A SEMIOTICS ANALYSIS OF STREET HARASSMENT ACTS REPRESENTATION IN L’ORÉAL’S CAMPAIGN - Zahrotul Nur Azizah Surya Putri (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2023)
Regarding the massive cases of sexual harassment, many companies tried to contribute to and support the stop sexual harassment movement by producing posters or video campaigns. Within those video campaigns released in the media, each has a profound meaning represented through graphic visualization, pictures, and sounds. Not only that, gestures, facial expressions, voice, or the language performed by the character in the illustration also brought many explicit meanings. Thus, this study aimed to reveal how the campaign video represents street sexual harassment and the messages to support each other or stand up against street harassment displayed by L'Oréal Paris in its campaign videos. From the analysis using Pierce's triangle of signs, the study revealed that street sexual harassment represented in the video into four types of street sexual harassment, namely suggestive comments, sexually explicit touch, inappropriate gestures, and being followed. However, society is not ready to face and combat street harassment. Thus, through the campaign video, L'Oréal brought some messages to educate society and encourage them to stand against street harassment.